Heterocyclic N-oxides - A Promising Class of Agents against Tuberculosis, Malaria and Neglected Tropical Diseases - dos Santos Fernandes, Guilherme F.; Pavan, Aline Renata; dos Santos, Jean Leandro (Current Pharmaceutical Design, 2018)
Heterocyclic N-oxides have emerged as promising agents against a number of diseases and disorders, especially infectious diseases. This review analyzes the emergence and development of this scaffold in the medicinal chemistry, focusing mainly on the discovery of new heterocyclic N-oxide compounds with potent activity against tuberculosis, malaria and neglected tropical diseases (i.e. leishmaniasis and Chagas disease). A number of heterocyclic N-oxides are described herein, nevertheless, the following chemical classes deserve to be highlighted due to a large number of reports in the literature about their promising pharmacological effects: furoxan, benzofuroxan, quinoxaline 1,4-di-N-oxide, indolone N-oxide and benzimidazole N-oxide. In order to describe those most promising compounds, we included in this review only those most biologically active heterocyclic Noxide published since 2000.
Keywords: leishmaniasis